Association between benzodiazepine outpatient treatment and risk of early seizure recurrence in emergency patients with seizure: A multicenter retrospective study. (23rd March 2021) - Roussel, Melanie; Chauvin, Anthony; Le Borgne, Pierrick; Drogrey, Marie; Eyer, Xavier; Hatabian, Ulysse; Choquet, Christophe; Peyrony, Olivier; Luhmann, Laura; Kassasseya, Christian; Belaud, Valentin; Navarro, Vincent; et al.
Abstract: Introduction: Seizures are one of the most common neurological reasons for emergency department (ED) visits. The benefit of ED‐initiated, short‐course outpatient benzodiazepine (BZD) treatment to prevent early recurrent seizure is unknown. This study assesses the risk of early seizure recurrence in patients who were or were not started with outpatient BZD in the ED. Methods: This was a multicenter retrospective study conducted in eight French EDs between January 1 and December 31, 2019. All patients admitted for seizure were retrospectively screened and those discharged home from the ED were included. Patients with a history of chronic alcohol intoxication or chronic BZD therapy were excluded. Baseline characteristics, type of seizure, and 30‐day outcome were retrospectively collected from the electronic health records. The primary endpoint was a return visit for seizure recurrence within 30 days. Independent factors associated with a seizure recurrence were identified using a multivariable binary logistic regression. Results: A total of 2, 218 patients were included and 1, 820 were analyzed. The median age was 39 years and 60% were men. Among them 82% of patients had a generalized tonic–clonic seizure and 47% of seizures were idiopathic. BZD treatment was started in 773 (42%) patients. A total of 154 (8%) patients had an early recurrence at 30 days: 68 (9%) in patients who were treated with BZD versus 86 (8%) in patients who were not (odds ratio [OR] = 1.07, 95% confidence interval [CI] = 0.71 to 1.43). In multivariable analysis, two factors were independently associated with the primary endpoint: chronic epileptic treatment (adjusted OR = 2.58, 95% CI = 1.55 to 4.37) and having had a focal seizure (adjusted OR = 2.16, 95% CI = 1.56 to 4.37). Conclusion: BZD therapy was started in 42% of patients who were discharged home after ED visit for a seizure. This treatment was not an independent factor associated with the risk of return visit for seizure recurrence at 30 days.